Analysis of Legality, Human Resources and Financial Inclusion on The Performance of MSMES - Dian, Cut; Lisnawati, Lisnawati; Fitriliana, Fitriliana; Lestari, Soraya; Dewi, Nuriza (Universitas Teuku Umar, 2025)
The success of MSMES measured through performance, which is influenced by legality, human resources (HR), and financial inclusion. Studies show that MSMEs with business legality tend to have increased financial performance compared to non-legal ones. Legality provides access to greater capital and fosters consumer confidence. Legal status is very important for MSMEs that want to grow, as it provides access to greater capital. A skilled workforce enhances professionalism and adaptability, which allows businesses to adopt financial inclusion with the latest technology. Financial inclusion gives individuals access to technologically charged financial services. Everyone deserves affordable, timely, and easy-to-use financial products to improve business continuity. This study aims to analyze how legality, human resources, and financial inclusion affect the performance of MSMEs. The method uses a qualitative approach, by filling out a questionnaire. The results of the study show that legality and financial inclusion significantly improve the performance of MSMEs, while human resources do not affect the performance of MSMEs. Financial inclusion makes decision-making better, allows MSMEs to choose the right financial services and meet their needs, and promotes well-being. Legality can foster consumer trust and loyalty, but human resources who are not professional and unable to adopt technology are not able to improve the performance of MSMEs and will be replaced by technology.